Optimization of seeding density in microencapsulated recombinant CHO cell culture - Zhang, Yuanyuan (Array, 2008)
Microencapsulation technology is an alternative large-scale mammalian cell culture method. The semi-permeable membrane of the microcapsule allows free diffusion of nutrients, oxygen and toxic metabolites to support cell growth, and the microcapsule membrane can protect the cells from the mechanical damage of shear forces associated with agitation and aeration. Many polymers have been used to make microcapsules, such as chitosan, polyacrylates, alginate, polyamino acids, and polyamides. One of these microcapsules is Alginate–polylysine–alginate (APA) microcapsule. Using the electrostatic droplet generator and polyelectrolyte complexation, we developed APA microcapsules with a diameter of 300 %m and assessed the effect of the seeding density on microencapsulated recombinant Chinese hamster ovary (CHO) cell growth, metabolism and endostatin production. The results showed that the cell growth was the best and endostatin production was the highest when the seeding density was 3 · 106 cells mL–1 microcapsule, at which the maximal cell density reached 1.82 · 107 cells mL–1 microcapsule and endostatin production reached 12.3 %g mL–1 at day 9. The energy metabolism was more efficient when the seeding density was 3 · 106 cells mL–1 microcapsule, at which more glucose and glutamine were utilized for biosynthesis and less lactate and ammonium were produced